Analisis Pendapatan Petani Nanas di Desa Tanjung Atap Kecamatan Tanjung Batu Kabupaten Ogan Ilir Analysis of Revenue of Pineapple Farmers in Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency - Eka Mulyana (Politeknik Negeri Lampung, 2017)
The purpose of this research are: (1) Calculate production cost and acceptance of pineapple farmer in Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency. (2) Calculating the income of pineapple farmers who have narrow land and large area in Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency. Data collected in this research are primary data and secondary data. Primary data obtained directly in the field by way of direct survey and field interviews with sample farmers using a list of questions that have been prepared. Secondary data are obtained from various institutions and agencies related to this research and the literature relating to this research. Sampling in Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency is Simple Random Sampling. Data obtained from the field survey results will be collected and processed systematically and will be analyzed in a desktiptive manner.The average pineapple fruit production per year is 1,8640 with the average selling price is Rp 1,555.24 in 3 (three) times the planting period per fruit so that the average revenue earned during one year is Rp. 29,422,142,86 per year. With an average variable cost and a flat fee of Rp. 11,631,571,43 and Rp. 73,764,28 so that farmers get net income from farming of Rp. 17.716.807,58.